PENGARUH PROFITABILITY, GROWTH OPPORTUNITY, DIVIDEND POLICY DAN FIRM SIZE TERHADAP CAPITAL STRUCTURE - Simamora, Deviana; Rasyid, Rosmita (Jurnal Paradigma Akuntansi, 2023)
This study aims to analyze the effect of profitability, growth opportunity, dividend policy, and firm size. The subjects in this study are manufacturing companies that have been listed on the IDX in 2017-2019 with the criteria of not having a loss, presenting financial statements in rupiah, and distributing dividends every year. Purposive sampling technique used in selecting research subjects as many as 37 companies. Data collection is based on time series data and cross section data. Time series data is taken based on the order of time while the cross section is taken based on company data in one period. Data analysis was performed with multiple regression analysis then the effect and relationship were analyzed by F test and t test. The results showed that the variable growth opportunity and dividend policy have no effect on capital structure. While the profitability variable has a negative effect on the capital structure and firm size variable has positve effect on capital structure. The implication of this research is company managers need to pay attention to and increase profits and company size in carrying out their performance so that the company is increasingly in demand by investors.